Expert System with Diagnosis of Blood Cancer (Leukaemia) with the Certainty Factor Method - S Silvilestari (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Blood cancer or called leukaemia usually affects children with a high risk of death. Lack of knowledge about leukaemia is the cause that affects parents to search for information. By looking at the condition of children who are still unable to think for themselves. Will make a concern for the people around him to help them overcome their problems. Parents or immediate family must supervise the child's development and development for the recovery of their child. To help the process of healing children who have leukaemia, parents must be active in seeking information about the disease. So that if there is a symptom, the parents are more sensitive. They can recognize and immediately prevent the leukaemia disease, in this study an application in the diagnosis of leukaemia is carried out using the help of an expert system which is used to assist in diagnosing leukaemia using certainty methods. Factor. The results of using the certainty factor method based on the symptoms and criteria possessed by patients with leukaemia patients will show a fairly high percentage and accuracy as a tool that shows the conditions experienced by people living with leukaemias.